What mode is conducive to an effective regional IP regime? Evidence from intellectual property courts in China - Lin Zou; Yiwen Zhu (Humanities & Social Sciences Communications)
Abstract Amid a patent boom and increase in patent infringement cases, China is a fast-growing catch-up country in the intellectual property (IP) regime, with arguments on effectiveness and standardization. In 2014, China installed three intellectual property courts (IPCs) in Beijing, Shanghai, and Guangzhou. This reform represents a crucial step in a series of reforms and actions that seek to establish a uniform and standardized judicial IP regime in China. Based on interviews, statistical reports, and an analysis of judicial documents, this study argues that the interpretation and execution of IP law vary across the three locations due to the embeddedness of those courts and their judges in the regions. Indications that the regional setting and presence of international firms affect the efficient proceedings of IP tribunals and courts were found as a result. Given that IP law is the same all over a country, it can be concluded that courts balance national regulation and regional realities.